Comparison of transradial coronary intervention for left main bifurcation disease using the new Braidin® slender 7 Fr sheath and a standard 6 Fr sheath. Issue 9 (September 2020) - Xu, Yingkai; Li, Yingkai; Yu, Jiancai; Wang, Deguang; Zhao, Qi; Cheng, Yujing; Zhou, Yujie
Objectives: To compare the effectiveness and safety of the Braidin® slender 7 Fr sheath with a standard 6 Fr sheath for treating left main bifurcation disease. Methods: From January 2017 to March 2019, 277 patients with left main bifurcation disease who underwent the transradial approach for percutaneous coronary intervention were divided into the slender 7 Fr sheath group (Braidin® slender 7 Fr sheath, n = 154) and standard 6 Fr sheath group (n = 123). Pathological features, surgical effect, and complications were evaluated. Results: The rate of using the classic crush technique was significantly higher in the slender 7 Fr sheath group than in the standard 6 Fr sheath group. The slender 7 Fr sheath group had a significantly shorter operation time than the standard 6 Fr sheath group. There were no significant differences in the radial artery occlusion rate after surgery and at 1 month of follow-up between the groups. Multivariate logistic regression analysis showed that 6 Fr and Braidin slender 7 Fr sheaths did not predict radial artery occlusion. Conclusion: The Braidin slender 7 Fr sheath has a superior operative process and similar safety for the radial artery as that of the standard 6 Fr sheath for treating left main bifurcation disease.